Exendin-4 alleviates β-Amyloid peptide toxicity via DAF-16 in a Caenorhabditis elegans model of Alzheimer's disease - Song, Xiangwei; Sun, Yingqi; Wang, Zhun; Su, Yingying; Wang, Yangkun; Wang, Xueli (Frontiers in Aging Neuroscience, 2022)
Epidemiological analyses indicate that type 2 diabetes mellitus (T2DM) is a risk factor for Alzheimer's disease (AD). They share common pathophysiological mechanisms. Thus, it has been increasingly suggested that several anti-T2DM drugs may have therapeutic potential in AD. Exendin-4, as a glucagon-like peptide-1 (GLP-1) receptor agonist, is an approved drug used to treat T2DM. In this research, the neuroprotective effect of Exendin-4 was investigated for the first time using transgenic Caenorhabditis elegans. Our results demonstrated that Exendin-4 attenuated the amyloid-β (1-42) (Aβ1-42) toxicity via multiple mechanisms, such as depressing its expression on protein and mRNA and reducing Aβ (1-42) accumulation. Exendin-4 at 0.5 mg/ml had been shown to extend life by 34.39% in CL4176 and delay the onset of paralysis in CL4176 and CL2006 which were increased by 8.18 and 8.02%, respectively. With the treatment of Exendin-4, the nuclear translocation of DAF-16 in the transgenic nematode TJ356 was enhanced. Superoxide dismutase-3 (SOD-3), as a downstream target gene regulated by DAF-16, was upregulated on mRNA level and activity. The reactive oxygen species (ROS) level was decreased. In contrast, we observed that the ability of Exendin-4 to regulate SOD was decreased in CL4176 worms with the DAF-16 gene silenced. The activity of SOD and the mRNA level of sod-3 were downregulated by 30.45 and 43.13%, respectively. Taken together, Exendin-4 attenuated Aβ (1-42) toxicity in the C. elegans model of AD via decreasing the expression and the accumulation of Aβ (1-42). Exendin-4 exhibited the ability of antioxidant stress through DAF-16. With continuous research, Exendin-4 would become a potential therapeutic strategy for treating AD.